2019
DOI: 10.1016/j.paid.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Voters rating politicians' personality: Evaluative biases and assumed similarity on honesty-humility and openness to experience

Abstract: The recent rise in controversial politicians has garnered substantial interest in the assessment of their personality. Observer ratings of politicians' personality, however, may suffer from evaluative and value-related biases. Evaluative biases are likely to differentially affect personality ratings of preferred and non-preferred politicians, whereas value-related biases are likely to affect ratings of honesty-humility and openness to experience of preferred politicians in line with the self-based heuristic or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The HEXACO Simplified Personality Inventory (HEXACO‐SPI; De Vries & Born, 2013; De Vries & Van Prooijen, 2019) is a 96‐item self‐report procedure for adolescents' scores on the HEXACO personality domains. The six HEXACO domains are measured with 16 items each, answered on a 5‐point Likert scale ranging from 1 ( strongly disagree ) to 5 ( strongly agree ): (1) Honesty‐Humility, with four items each for the facets sincerity, fairness, greed avoidance, and modesty; (2) Emotionality, with four items each for the facets fearfulness, anxiety, sentimentality, and dependence; (3) eXtraversion, with four items each for the facets social self‐esteem, social boldness, sociability, and liveliness; (4) Agreeableness, with four items each for the facets patience, forgiveness, gentleness, and flexibility; (5) Conscientiousness, with four items each for the facets organization, diligence, perfectionism, and prudence; and (6) Openness (to Experience), with four items each for the facets aesthetic appreciation, inquisitiveness, unconventionality, and creativity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HEXACO Simplified Personality Inventory (HEXACO‐SPI; De Vries & Born, 2013; De Vries & Van Prooijen, 2019) is a 96‐item self‐report procedure for adolescents' scores on the HEXACO personality domains. The six HEXACO domains are measured with 16 items each, answered on a 5‐point Likert scale ranging from 1 ( strongly disagree ) to 5 ( strongly agree ): (1) Honesty‐Humility, with four items each for the facets sincerity, fairness, greed avoidance, and modesty; (2) Emotionality, with four items each for the facets fearfulness, anxiety, sentimentality, and dependence; (3) eXtraversion, with four items each for the facets social self‐esteem, social boldness, sociability, and liveliness; (4) Agreeableness, with four items each for the facets patience, forgiveness, gentleness, and flexibility; (5) Conscientiousness, with four items each for the facets organization, diligence, perfectionism, and prudence; and (6) Openness (to Experience), with four items each for the facets aesthetic appreciation, inquisitiveness, unconventionality, and creativity.…”
Section: Methodsmentioning
confidence: 99%
“…The six HEXACO domains are measured with 16 items each, answered on a 5‐point Likert scale ranging from 1 ( strongly disagree ) to 5 ( strongly agree ): (1) Honesty‐Humility, with four items each for the facets sincerity, fairness, greed avoidance, and modesty; (2) Emotionality, with four items each for the facets fearfulness, anxiety, sentimentality, and dependence; (3) eXtraversion, with four items each for the facets social self‐esteem, social boldness, sociability, and liveliness; (4) Agreeableness, with four items each for the facets patience, forgiveness, gentleness, and flexibility; (5) Conscientiousness, with four items each for the facets organization, diligence, perfectionism, and prudence; and (6) Openness (to Experience), with four items each for the facets aesthetic appreciation, inquisitiveness, unconventionality, and creativity. The full questionnaire and validity information can be found elsewhere (De Vries & Born, 2013; De Vries & Van Prooijen, 2019; De Vries et al, 2020). Final variables were calculated as the average sum score for all domain items.…”
Section: Methodsmentioning
confidence: 99%
“…Political science can also be benefited from nuancing the process of personalisation by follower-centric models. Recent research has shown that people evaluate preferred and non-preferred politicians (De Vries and Van Prooijen, 2019) differently, contributing to negative personalisation (Garzia and da Silva, 2021). Partisanship further complicates this picture.…”
Section: Discussionmentioning
confidence: 99%
“…We also explored whether masking and cancellation effects occurred in the prediction of likeability and popularity, providing a better understanding of the underlying behaviours involved in becoming likeable and popular. The strength of this study is that we relied on self-ratings of personality among adolescents using the recently developed HEXACO-SPI (De Vries & Born, 2013;De Vries & Van Prooijen, 2019) and on peer nominations of both likeability and popularity, thus providing independent assessments of the key variables in our study.…”
Section: The Present Studymentioning
confidence: 99%
“…One of the reasons for this lack of research has been the fact that-until recently-no instrument was available to measure HEXACO personality among early adolescents. In this study, we will use the recently developed HEXACO Simplified Personality Inventory (HEXACO-SPI;De Vries & Born, 2013;De Vries & Van Prooijen, 2019)-which was constructed to be used among (early and late) adolescents and among adults with lower language proficiency levels-to investigate the differential relations of HEXACO traits with sociometric measures of likeability and popularity among early adolescents. This study adds to previous research by (i) investigating the relations between honestyhumility and both likeability and popularity when controlling for the other five HEXACO personality domain-level traits, (ii) investigating whether gender, agreeableness, and extraversion interact with honesty-humility in the prediction of likeability and popularity, (iii) investigating whether broad traits and facets differentially relate to these two sociometric measures, and (iv) investigating whether masking and cancellation effects occur within HEXACO domains in the facet-level associations with likeability and popularity.…”
mentioning
confidence: 99%